IMPLIKASI KULINER SESAJI DAN DHANYANG DALAM UPACARA TRADISI DI JEPARA - Sri Indrahti; Siti Maziyah; Alamsyah Alamsyah; Yanuar Yoga Prasetyawan (Berkala Arkeologi, 2019)
The article describes the culinary imp lic ation of offerings and d hanyang in 5 (five) villages in Jepara in the form of traditional ceremonies of Jembul Tulakan, Hari Jadi Kota Jepara, Sedekah Laut, Perang Obor, and Pesta Baratan. Only three out of five ceremonies were present ing culinary offerings as a representation of the dhanyang presence. The objective of this study is to reveal the existence of culinary offerings and d hanyang both by their food types and the intended dh anyang. This study was using a qualitative method which includes the collection of primary and secondary sources through literature study, observation, participants, structured interviews, indepth interviews, and Focus Group Discussion. The approaches which were used are anthropological and hermeneutical approaches. The study reveals a symbolic meaning from the presence of various culinaries presented to dhanyang and wishes expressed implicitly or explicitly in the ceremony. The wishes include the requests of safety, kindness, protection, etc. Recently, these wishes have shifted which caused by better knowledge, belief, and social experience of the performers towards their religion. Public belief in the power of d hanyang still exists even though it is not dominant.